(untitled) - Allemang, Dean (Amsterdam,Boston, 2008)
The promise of the Semantic Web to provide a universal medium to exchange data information and knowledge has been well publicized. There are many sources too for basic information on the extensions to the WWW that permit content to be expressed in natural language yet used by software agents to easily find, share and integrate information. Until now individuals engaged in creating ontologies-- formal descriptions of the concepts, terms, and relationships within a given knowledge domain-- have had no sources beyond the technical standards documents.
Keywords: Metadata,Semantic Web,Siêu dữ liệu,Web ngữ nghĩa